The Critical Engagement with Modern Knowledge in the Writings of Malek Bennabi - Benlahcene, Badrane (Journal of Al-Tamaddun, 2024)
This paper explores the intellectual contributions of Malek Bennabi, focusing on his engagement with modern knowledge, and its implications for addressing the challenges faced by Muslim civilization. It examines Bennabi’s critical perspective on the interpretations of history, the social sciences, Western Centrism, and the modernity discourse, and how his approach reflects both a creative openness to diverse fields of knowledge and a critical stans to their worldviews, concepts methodologies, and end products. The paper finds that by integrating modern knowledge advancements while maintaining a critique of their underlying assumptions, Bennabi aimed to lay the groundwork for social and civilizational renewal within the Muslim Ummah. His work advocates for a balanced approach, combining critical dialogue between modern Western knowledge and Islamic worldview, heritage, and teachings, to overcome stagnation and activate the civilizational potential of Muslim societies in the modern era.